Pengaruh Admixture Terhadap Campuran Beton K 350 Ditinjau Dari Kuat Tekan Beton - Rida Respati (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
In this research, we want to experiment to find out the compressive strength of medium quality concrete K-350 with ingredients added MASTER RHEOBUILD 6, whose function is to accelerate hardening, improve the quality of concrete, reduce water use and increase the value of slump. However, it should be noted that errors in dosages and how to use added ingredients can be detrimental to the quality of concrete. The results of the study show that the addition of 0.25, 0.5 and 0.75 liters per 50 kg of cement can increase the concrete compressive strength. The compressive strength of concrete with the addition of 0.25 liters/50 kg of cement has increased 362.67 kg/cm² from the normal concrete compressive strength of 350.58 kg/cm2. The addition of 0.5 liters/50 kg of cement has increased again to 373.24 kg/cm², and the addition of 0.75 liters/50 kg of cement has increased the concrete compressive strength to 379.29 kg/cm² of normal concrete. Comparison of compressive strength before and after addition of admixture with an increase of 3.45% in addition of 0.25 liters/50 kg of cement, 6.47% in addition of 0.5 liters/50 kg of cement and 8.19% in addition of 0.75 liters/50 kg of cement.